Caseins micelles crosslinked with transglutaminase: foaming properties as a function of pH - Devaud, Atalita dos Santos (2019)
Caseins represents 80% of the cow”s milk proteins and are widely used 1n food industry due to their recognized foaming properties. The casein term refers to a mixture of four different casein fractions known as asl, as2, B, and K-caseim that are organized m structures called casei micelles (CMs). The foam properties of casei micelles are closely related to their structure, which 1s influenced by several factors, including pH variations. In this context, enzymatic crosslinking with transglutaminase (Tgase) can increase the stability of CMs against pH collapse. This work imitially does a review on foam structure and the main factors influencing the CMs structure and 1ts relation to foam stabihty. In addition, it approaches how Tgase enzymatic crosslinking increase CMs stabihty against pH variations. The hypothesis of expanding the use of CMs as foam stabilizers by Tgase crosslinking was raised. Thus, the objective of this study was to compare pH stability of CMs cross-linked with Tgase (CMs-Tgase) and native CMs, concerning foam stability. Different suspensions of native CMs (MCS-CMs) and CMs- Tgase (MCS-CMs-Tgase) were prepared at 27.5 g/L in deionized type 1 water with 2 mM CaCl». The ssamples were acidified at pH values ranging from pH 7.0 to pH 2.0, at intervals of 0.5. The samples obtamed were analyzed im terms of particle size, charge, surface tension, absorbance and foam stability. Tgase did not induce to a significant difference between the diameter of native CMs and CMs-Tgase. However, It led to greater stability in acid destabilization: while native CMs precipitated below pH 5.5, CMs- Tgase precipitated only from pH 3.5 to 4.5. This occurred nm part due to the change mm the isoelectric point (pI) of the CMs-Tgase, pH 4.7 (found for native CMs) to pH 4.3. Foams with MCS-CMs-Tgase presented higher half-lfe time than those with MCS- CMs from pH 5.0 to 2.0, forming foams that last for 48 hours at pH 5.0. The MCS- CMs-Tgase foams had lower half-lfe time at pH 7.0 to 5.5, compared to the MCS- CMs foams. The higher half-hfe time at pH 5.0 to 2.0 can be attributed to a greater amount of dispersed CMs and small suspended aggregates, which, because of particle size and protemm concentration, were able to prolong the lhfe of foams interfacial films. In relation to the lower stability found 1n the range of pH 7.0 to 5.5, It can be explained by the reduction of the amount of CMs able to unfold the air- water interfaces due to crosslinking, and to repulsive forces between particles at air/ water Interface.